Prowadzenie działalności gospodarczej w Polsce : czy wszyscy cudzoziemcy traktowani są na równych zasadach? - Gutierrez, Patryk (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2023)
With regard to the legal possibility of running a business in Poland, this paper addresses the question: are all foreigners treated on an equal basis? The analysis of legal regulations has shown that some foreigners may undertake and conduct business activities on the same terms as Poles. While, other foreigners may run a business within the scope legally assigned to them. It can be noticed that the restrictions related to taking up and pursuing business activity by foreigners in Poland are a consequence of their failure to meet certain legal requirements related to, for example, citizenship or a temporary residence permit.
Keywords: business activity; foreigners; citizens of the European Union Member States; the principle of equality before the law; prohibition of discrimination